Pelatihan dan Pendampingan Kader Kesehatan melalui Media Flashcard untuk Meningkatkan Kesadaran Herbavigilans dan Rasionalitas Penggunaan Tanaman Obat [ Training and Assistance of Health Cadres through Flashcard Media to Increase Awareness of Herbavigilance and the Rationality of the Use of Medicinal Plants] - Atmaja, Dewi Susanti; Rohama, Rohama; Latif, Abdul; Raihanah, Raihanah; Tazkiyah, Aulia; Nurhidayah, Dea; Aulia, Devina; Khatimah, Husnul; Yuniar, Nabila; Dagau, Lelie; Syifha, Nor; Amelia, Rina; Gunawan, Prayogo Aldi; Abidin, Zainul (UKInstitute, 2026)
This community service activity was carried out in Danda Jaya Village, Rantau Badauh District, Barito Kuala Regency, with the aim of increasing awareness of herbavigilance and rationality of the use of medicinal plants among the community. This program uses a Participatory Action Research (PAR) approach that emphasizes the activity involvement of the community in every stage of the activity. The target of the activity consisted of Posyandu cadres with a total of 20 participants. The implementation of the activity lasted for three months and included three main stages, namely preparation, implementation, and evaluation. In the preparation stage, coordination was carried out with the village government and an initial survey regarding the types and patterns of use of medicinal plants. The implementation stage included counseling, training and mentoring, as well as the formation of the Danda Jaya Village Herbavigilance Monitoring Group as an effort to sustain the program. The results of the evaluation showed that there was a significant increase in the average value of cadre knowledge from 49,5 ± 13.17 to 82.0 ± 9.51, with an increase of 32.5% and a statistically significant difference (p less than 0.001). The distribution of categories shows a large shift from the “less” to the “good” and “excellent” levels. Before the training, the majority of cardes (85%) were in the “less” and “sufficient” categories, while after the training, 85% had reached the “good” to “very good” category. These results prove that herbavigilance-based training with the support of flashcard media is effective in increasing cardes understanding of the safety of using medicinal plants safely and rationally. Although the increase is not too large, this activity has succeede in fostering a new understanding of the importance of monitoring the side effects of medicinal plants and encouraging the public to be more careful in their use. This program has proven to be effective in educating the community while strengthening the role of villages as active actors in maintaining health based on local potential. Abstrak. Kegiatan pengabdian kepada masyarakat ini dilaksanakan di Desa Danda Jaya, Kecamatan Rantau Badauh, Kabupaten Barito Kuala, dengan tujuan meningkatkan kesadaran herbavigilans dan rasionalitas penggunaan tanaman obat di kalangan masyarakat. Program ini menggunakan pendekatan Participatory Action Research (PAR) yang menekankan keterlibatan aktif masyarakat dalam setiap tahapan kegiatan. Sasaran kegiatan terdiri dari kader posyandu dengan total peserta sebanyak 20 orang. Pelaksanaan kegiatan berlangsung selama tiga bulan dan mencakup tiga tahapan utama, yaitu persiapan, pelaksanaan, dan evaluasi. Pada tahap persiapan dilakukan koordinasi dengan pemerintah desa serta survei awal mengenai jenis dan pola penggunaan tanaman obat. Tahap pelaksanaan mencakup penyuluhan, pelatihan dan pendampingan, serta pembentukan Kelompok Pemantau Herbavigilans Desa Danda Jaya sebagai upaya keberlanjutan program. Hasil evaluasi menunjukkan adanya peningkatan nilai rata-rata pengetahuan kader meningkat signifikan dari 49,5 ± 13,17 menjadi 82,0 ± 9,51, dengan peningkatan sebesar 32,5% dan perbedaan yang bermakna secara statistik (p kurang dari 0,001). Distribusi kategori menunjukkan pergeseran besar dari tingkat “kurang” ke “baik” dan “sangat baik”. Sebelum pelatihan, mayoritas kader (85%) berada pada kategori “kurang” dan “cukup”, sedangkan setelah pelatihan, 85% sudah mencapai kategori “baik” hingga “sangat baik”. Hasil ini membuktikan bahwa pelatihan berbasis herbavigilans dengan dukungan media flashcard efektif dalam meningkatkan pemahaman kader tentang keamanan penggunaan tanaman obat secara aman dan rasional. Meskipun peningkatannya tidak terlalu besar, kegiatan ini berhasil menumbuhkan pemahaman baru tentang pentingnya pengawasan terhadap efek samping tanaman obat serta mendorong masyarakat untuk lebih berhati-hati dalam penggunaannya. Program ini terbukti efektif dalam mengedukasi masyarakat sekaligus memperkuat peran desa sebagai pelaku aktif dalam menjaga kesehatan berbasis potensi lokal.